Evaluation of a chloride-based (89)Zr isolation strategy using a tributyl phosphate (TBP)-functionalized extraction resin - Graves, Stephen A. (Nucl Med Biol, 2018)
INTRODUCTION: The remarkable stability of the (89)Zr-DOTA complex has been shown in recent literature. The formation of this complex appears to require (89)Zr-chloride as the complexation precursor rather than the more conventional (89)Zr-oxalate. In this work we present a method for the direct isolation of (89)Zr-chloride from irradiated (nat)Y foils. METHODS: (89)Zr, (88)Zr, and (88)Y were prepared by 16 MeV proton irradiation of (nat)Y foils and used for batch-extraction based equilibrium coefficient measurements for TBP and UTEVA resin. Radionuclidically pure (89)Zr was prepared by 14 MeV proton-irradiation of (nat)Y foils. These foils were dissolved in concentrated HCl, trapped on columns of TBP or UTEVA resin, and (89)Zr-chloride was eluted in < 1 mL of 0.1 M HCl. For purposes of comparison, conventionally-isolated (89)Zr-oxalate was converted to (89)Zr-chloride by trapping, rinsing, and elution from a QMA cartridge into 1 M HCl. Trace metal analysis was performed on the resulting (89)Zr products. RESULTS: Equilibrium coefficients for Y and Zr were similar between UTEVA and TBP resins across all HCl concentrations. K(d) values of less than 10(−1) mL/g were observed for Y across all HCl concentrations. K(d) values of greater than 10(3) mL/g were observed at HCl concentrations greater than 9 M for Zr, falling to K(d) values of less than 10° mL/g at low HCl concentrations. (89)Zr-chloride was recovered from small columns of TBP in <1 mL of 0.1 M HCl with an overall recovery efficiency of 89±3% (n=3). An average Y/Zr separation factor of 1.5 × 10(5) (n=3) was obtained. Trace metal impurities, notably Fe, were higher in TBP-isolated (89)Zr-chloride compared with (89)Zr-chloride prepared using the conventional two-step procedure. CONCLUSION: TBP-functionalized resin appears promising for the direct isolation of (89)Zr-chloride from irradiated (nat)Y targets. Excellent (89)Zr recovery efficiencies were obtained, and chemical purity was sufficient for proof-of-concept chelation studies.